Managing Segmental Renal Diseases - Rocca Rossetti, Salvatore (Springer International Publishing, 2018)
This volume focuses on those rare congenital or acquired kidney pathologies that are localized in only one part of the organ, while the rest of the organ remains unaffected. It helps readers identify the segmentary stage of the disease and discusses in-depth possible conservative surgical approaches: partial nephrectomy, calicectomy and lobectomy. It is a valuable resource for urologists, nephrologists and surgeons as well as researchers and practitioners involved in the field.